2021
DOI: 10.1039/d1tc00068c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electron transporting and panchromatic absorbing FRET cassettes based on aza-BODIPY and perylenediimide towards multiple metal FRET-Off sensing and ratiometric temperature sensing

Abstract: Multichromophoric triads 1 and 2 based on aza-BODIPY as central chromophore and bay-substituted (tetrachloro- and tetraphenoxy-)perylenediimides (PDI) as peripheral chromophores have been designed and synthesized that are panchromatic absorbers and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Accordingly, a large class of multichromophoric donor-acceptor systems have been designed and their dynamics of energy/electron transfer have been probed in the context of biomimetic photosynthetic systems and also optoelectronic applications. [9][10][11][12] BODIPY dyes with their synthetic versatility, high absorption coefficient, absorption in the visible region (350-650 nm), thermal and photochemical stability and high charge carrier mobility are ideal candidates for artificial LH systems. 13 The efficiency of light-harvesting can be enhanced by harnessing excitonic coupling among the chromophores, which has been recently reported for cyclic BODIPY derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a large class of multichromophoric donor-acceptor systems have been designed and their dynamics of energy/electron transfer have been probed in the context of biomimetic photosynthetic systems and also optoelectronic applications. [9][10][11][12] BODIPY dyes with their synthetic versatility, high absorption coefficient, absorption in the visible region (350-650 nm), thermal and photochemical stability and high charge carrier mobility are ideal candidates for artificial LH systems. 13 The efficiency of light-harvesting can be enhanced by harnessing excitonic coupling among the chromophores, which has been recently reported for cyclic BODIPY derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the aza-BODIPY moiety in FRET cassettes undergo a redox transformation in the presence of Fe 3+ and Co 2+ that leads to the depletion of its absorption band due to radical cation/anion generation leading to a ratiometric FRET turn-off sensing behavior. 68 …”
Section: Resultsmentioning
confidence: 99%
“…Previously we have elucidated that the sensing of Co 2+ and Fe 3+ sensing by aza-BODIPY is a redox-driven process. 68 The same rationale can be applied to Co 2+ , since it can readily adopt +2 or +3 states and can therefore participate in charge transfer processes to or from aza-BODIPY. The plausible mechanism for Co 2+ /Fe 3+ ions sensing is provided in the ESI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the chemistry of BODIPY is actively devel oping, and every year, new compounds and groups of substances appear that are appli cable to solve problems in medicine [23], sensorics, including biosensorics [24], and in the design of new optical energy converters [25][26][27]. The list of measured parameters is exten sive and includes temperature [28], the viscosity [29] of intracellular and intercellular flu ids, the shape and volume of organelles [30], the presence of heavy metal ions [31], and the acidity of the medium [32]. The study of these parameters is closely connected with solvent polarity and dye solvatochromism [33][34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%